Pengembangan Desain Permainan Stik Lalaran untuk Peningkatan Kemampuan Mufrodat dalam Kitab Bahasa Arab Ro’sun Sirah bagi Santri Madrasah Diniyah Tingkat Ula - Mochamad Hasyim; Amang Fathurrohman (Universitas Yudharta Pasuruan, 2018)
Indonesia is one of the largest Muslim countries in the world. So that the existence of Arabic in Indonesia becomes one of the important languages ​​to be studied and mastered by Indonesian people. Therefore, the Arabic language has been taught in various educational institutions, especially Islamic religious education institutions in the Islamic Middle School. A variety of Arabic books taught to students of the Islamic School, one of them is the Book of Arabic Ro'sun Sirah. In this study, the author will explain the development of the design of the runway sticks Ro'sun Sirah game as one of the media to make it easier for student of the Islamic School to learn the Book of Arabic in Ro'sun Sirah. With the development method using the ADDIE approach, the authors succeeded in developing a variety of designs on the runnings of Ro'sun Sirah sticks; Among them is the game “Jungkat-Jungkit Stik”, game “Tepuk Stik”, game “Undian Stik”, game “Kopyok Stik”, game “Meraba Stik”, game Stik “Putar Jam Penebak”, game “Hunting Kata Dalam Stik”, and game “Comot Stik”.